Transhyoid approach in surgical treatment of oropharyngeal carcinoma - A. V. Karpenko; R. R. Sibgatullin; А. А. Boyko; М. G. Kostova (Опухоли головы и шеи)
The study objective is to assess functional and oncologic results of transhyoid approach used for surgical treatment of oropharyngeal carcinoma.Materials and methods. Operative records, hospital charts and data from out-patient department of 55 patients (T1 – 6, T2 – 16, T3 – 19, T4 – 14) with oropharyngeal carcinoma operated via a transhyoid approach were reviewed. Postoperative period was reviewed for complications. All oncologic adverse events were registered with special emphasis on the rate of local recurrence. A univariate analysis with chisquare and Fisher’s exact test was used to check the correlation between tumor factors and surgical variables (complications, mode of reconstruction). The influence of tumor- and treatment-related variables (T stage, differentiation, perineural invasion, p16 status, depth of invasion, extension to the oral cavity, adjuvant treatment) on the rate of local recurrence was studied in the same way. The log-rank test was used to assess differences in survival curves. The data was compared with other series of patients treated with the same technique.Results. Seventeen (30,9 %) patients developed 29 complications. There was 1 postoperative death. Five (9,1 %) patients required repeated operation. The mode of reconstruction (primary closure vs flaps) was a major factor influencing the rate of complications. Fifty (92,6 %) patients were able to resume oral diet with a duration of nasogastric tube feeding of 7–35 days. Three-year overall/disease-specific survival for the whole cohort were 47 and 51,1 %, for p16-positive (22 %) cohort – 65,6 and 87,5 %, for p16-negative (78 %) cohort – 40,6 and 46,8 %. Thirteen (24 %) patients developed a local recurrence. The rate of local recurrence was negatively affected by p16 negativity (p = 0,048), depth of invasion >10 mm (p = 0,044) and depth of invasion >15 mm (p = 0,003).Conclusion. Transhyoid approach may be considered as a surgical option for treatment of oropharyngeal carcinoma with acceptable rate of complications.